High-resolution reconstruction of sea-ice and hydrological conditions in the south-eastern Laptev Sea during the Holocene deduced from microalgae assemblages - Polyakova, Yelena; Klyuvitkina, Tatiana; Bauch, Henning; Kassens, Heidemarie (UNIS, 2011)
The Laptev Sea constitutes the central part of the wide Siberian shelf and is regarded as a key area for the freshwater and sea-ice balances of the Arctic Ocean. More than a quarter of the total continental freshwater runoff to the Arctic Ocean is discharged into the Laptev Sea, mainly via the Lena River (Gordeev, 2000). Furthermore, the Laptev Sea polynya is a major source area for sea ice, which is transported to the Siberian branch of the Transpolar Drift (e.g., Zakharov, 1996). Therefore, knowledge of the Holocene variability of the Laptev Sea hydrology is essential for understanding Arctic Ocean water circulation in the past. Our paleoenvironmental reconstructions based on a detailed study on diatom and aquatic palynomorph assemblages and a detailed radiocarbon (AMS 14 C) chronology of sediment cores obtained from the south-eastern Laptev Sea adjacent to the Lena River Delta. Established linkages between hydrographical parameters (e.g., summer surface-water salinity, sea-ice conditions, Polyakova, 2003; Klyuvitkina, Bauch, 2006) and the composition of surface-sediment diatom and aquatic palynomorph assemblages were used to reconstruct environmental conditions under postglacial sea-level rise and climatic changes. Our records give evidences for inundation of the outer Laptev Sea shelf (> 51 m water depth) approximately 11.3 cal. ka. River-proximal environment characterized by avalanche-like precipitation of river-loaded matter (“marginal filter”) under water salinity <9. The time interval 10.7-9.2 cal. ka was marked by enhanced influence of Atlantic Water on the Laptev Sea hydrology. Because a continuously rising sea level resulted in the southward retreating coastline, surface-water salinities on the outer shelf approached modern values of about 15-16 around 8.6 cal. ka. Approximately 8.9-8.5 cal. ka, when the sea-level reached the position of the present-day isobaths of about 32-30 m, the inner-shelf was flooded. On the inner Laptev Sea shelf, modern-like environmental conditions were reached about 1 ...